First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Clockwise hysteresis of diatoms in response to nutrient dynamics during eutrophication and recovery - Manuela Milan; Nina Albrecht; Frank Peeters; Simone Wengrat; Martin Wessels; Dietmar Straile (Limnology and Oceanography, 2022)
Many lake ecosystems that have been severely disturbed by eutrophication, have also experienced large human efforts to restore “natural” conditions. However, the trajectories and the extent of recovery of these lake ecosystems are still poorly understood. In many shallow lakes, recovery was often delayed and counter‐clockwise hysteretic. Here, we study recovery and ecosystem trajectories in a large and deep lake using diatom remains in sediment cores and time series of phosphorus concentrations. We identified four periods of diatom community change: slow change during early eutrophication, thereafter a short period of rapid change after the 1950s, followed by community stability from the 1960s to the mid‐1980s, and finally a recovery phase until 2010. Diatom community structure responded quickly and in a saturating way to increasing phosphorus concentrations, but also fast to phosphorus decline. Hence, diatom community dynamics did not show counter‐clockwise hysteresis but was characterized by a high degree of recovery and clock‐wise hysteresis (CWH). We suggest that CWH in response to eutrophication and recovery is a typical and previously overlooked feature of deep lakes, which results from a more rapid change of average nutrient concentrations and thus productivity in the epilimnion compared to average nutrient concentrations across the entire water column. Such nonlinear and hysteretic responses to changing nutrients need to be considered when analyzing the effects of other stressors such as climate warming on ecosystem dynamics to prevent erroneous attribution of ecosystem change to other stressors instead of nutrient change.

Examining the sources of variability in cell culture media used for biopharmaceutical production - Nicola McGillicuddy; Patrick Floris; Simone Albrecht; Jonathan Bones (Biotechnology Letters, 2018)

Mapping global cropland and field size - Steffen Fritz; Linda See; Ian McCallum; Liangzhi You; Andriy Bun; Elena Moltchanova; Martina Duerauer; Fransizka Albrecht; Christian Schill; Christoph Perger; Petr Havlik; Aline Mosnier; et al. (Global Change Biology, 2015)
A new 1 km global IIASA ‐ IFPRI cropland percentage map for the baseline year 2005 has been developed which integrates a number of individual cropland maps at global to regional to national scales. The individual map products include existing global land cover maps such as GlobCover 2005 and MODIS v.5, regional maps such as AFRICOVER and national maps from mapping agencies and other organizations. The different products are ranked at the national level using crowdsourced data from Geo‐Wiki to create a map that reflects the likelihood of cropland. Calibration with national and subnational crop statistics was then undertaken to distribute the cropland within each country and subnational unit. The new IIASA ‐ IFPRI cropland product has been validated using very high‐resolution satellite imagery via Geo‐Wiki and has an overall accuracy of 82.4%. It has also been compared with the EarthStat cropland product and shows a lower root mean square error on an independent data set collected from Geo‐Wiki. The first ever global field size map was produced at the same resolution as the IIASA ‐ IFPRI cropland map based on interpolation of field size data collected via a Geo‐Wiki crowdsourcing campaign. A validation exercise of the global field size map revealed satisfactory agreement with control data, particularly given the relatively modest size of the field size data set used to create the map. Both are critical inputs to global agricultural monitoring in the frame of GEOGLAM and will serve the global land modelling and integrated assessment community, in particular for improving land use models that require baseline cropland information. These products are freely available for downloading from the http://cropland.geo-wiki.org website.

Report on the annual meeting of the working groups ‘Mycology’ and ‘Host-Parasite-Interactions’ of the German Scientific Society for Plant Protection and Plant Health r. S. - Ralf Vögele; Ulrike Steiner; Frank Albrecht; Lars Leichert; Alan Slusarenko; Jens Bojahr; Ottilia Nhengiwa; Björn Rotter; Nicolas Krezdorn; Brigitte Ruge-Wehling; Christine Struck; Peter Winter; et al. (Journal of Plant Diseases and Protection, 2014)

A HPLC-based glycoanalytical protocol allows the use of natural O-glycans derived from glycoproteins as substrates for glycosidase discovery from microbial culture - Li Liu; Tharmala Tharmalingam; Eva Maischberger; Simone Albrecht; Mary E. Gallagher; Raúl Miranda-CasoLuengo; Wim G. Meijer; Pauline M. Rudd; Jane A. Irwin (Glycoconjugate Journal, 2013)

A secondary metabolite of Brassicales, 1-methoxy-3-indolylmethyl glucosinolate, as well as its degradation product, 1-methoxy-3-indolylmethyl alcohol, forms DNA adducts in the mouse, but in varying tissues and cells - Fabian Schumacher; Simone Florian; Anke Schnapper; Bernhard H. Monien; Inga Mewis; Monika Schreiner; Albrecht Seidel; Wolfram Engst; Hansruedi Glatt (Archives of Toxicology, 2013)